Peran dan etika hubungan stakeholders di bidang pendidikan - Saputra, Micho Triana (Maliki Interdisciplinary Journal, 2024)
Education is one of the aspects in producing the next generation of the future for progress in the State of Indonesia. Synergy from various parties or stakeholders will certainly affect the success of an educational institution. Good collaboration between stakeholders contributes positively to the quality of education and student welfare. In addition, ethical principles such as transparency, accountability, fairness and social responsibility prove crucial in building mutually beneficial and sustainable relationships. The results of the discussion explain the mapping, roles and strategies in building stakeholder relationships in education.